2023
DOI: 10.1029/2022jb025225
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inversion of Finite‐Fault Earthquake Slip Model Using Geodetic Data, Solving for Non‐Planar Fault Geometry, Variable Slip, and Data Weighting

Abstract: Evaluating seismic hazard and understanding earthquake preparation processes require precise fault slip models which characterize the fault geometry and slip distribution. A precise fault slip model can assist in probing the accumulation and release of stress as well as the frictional behavior on the fault (Caniven et al., 2017;Collettini et al., 2011;Manighetti, 2005). Over the past decades, the temporal and spatial resolutions of the geodetic techniques which measure ground deformation have been significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Many other fault properties could also influence the resulting simulated earthquake statistics, including slip rake (slip direction), normal and shear stress conditions, fault frictional properties and fault roughness, all of which are here assumed to be homogeneous along the fault surfaces. A recent study of Bayesian finite‐fault inversion has shown that variable fault slip directions allow better determination of the nonplanar fault geometries associated with large earthquakes (Wei et al., 2023). In addition, frictional properties of large seismogenic faults may vary spatially and/or temporally (e.g., before, during, and after an earthquake).…”
Section: Discussionmentioning
confidence: 99%
“…Many other fault properties could also influence the resulting simulated earthquake statistics, including slip rake (slip direction), normal and shear stress conditions, fault frictional properties and fault roughness, all of which are here assumed to be homogeneous along the fault surfaces. A recent study of Bayesian finite‐fault inversion has shown that variable fault slip directions allow better determination of the nonplanar fault geometries associated with large earthquakes (Wei et al., 2023). In addition, frictional properties of large seismogenic faults may vary spatially and/or temporally (e.g., before, during, and after an earthquake).…”
Section: Discussionmentioning
confidence: 99%
“…Driven by its strengths in probabilistic inference, Bayesian probability theory is gaining considerable traction in earthquake science for tackling complex models. By synergistically integrating historical seismic data, geological information, and real-time monitoring data, Bayesian models refine earthquake probability estimates and illuminate the intricate interplay between stress accumulation, fault geometry, and seismic release [24]. Notably, the Bayesian approach has been applied in various contexts within earthquake forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…Inversions of geodetically ground displacements are exclusively capable of determining the most plausible fault geometry at depth (Bagnardi & Hooper, 2018; Wei, Chen, Lyu, et al, 2023; Wei, Chen, & Meng, 2023). In this study, the seismogenic fault geometry is estimated through a fully Bayesian inversion of the co‐seismic ground displacements, informed by the interferometric synthetic aperture radar (InSAR) approach.…”
Section: Introductionmentioning
confidence: 99%